Effects of COVID-19 Lockdown on Body Composition and Physical Performance of Elite Female Football Players - Villaseca-Vicuña, R.; Pérez-Contreras, J.; Merino-Muñoz, P.; Aedo-Muñoz, E.; Jurado, J. A. G.; Zabaloy, S. (Women in Sport and Physical Activity Journal, 2022)
The COVID-19 pandemic led to an unusual situation in sports. Players were forced to stay at home for an undefined period of time and not allowed to use any training facilities or even exercise outdoors. Therefore, this study aimed to examine the effects of the COVID-19 lockdown on physical performance and body composition in elite female football players. During the confinement period, 19 players (n = 19, M = 27 years; SD = 4.19) volunteered to participate in the present study. Participants were confined during 5 months and performed six remotely guided sessions a week, designed and structured by a certified fitness coach. Pre- and postconfinement period, players were tested for body composition, strength in the squat exercise, vertical jump, 30-m sprint, kicking velocity, and intermittent endurance capacity (Yo-Yo Intermittent Recovery Level 1). Fat mass and muscle mass remained unaffected after the confinement period, while only body mass showed a significant increase between periods (1.19%; p = .014). In addition, physical performance measures postconfinement showed positive changes in kicking (p < .001; effect size = 1.02), in contrast to a reduction in mean propulsive velocity against 40-kg load and Yo-Yo Intermittent Recovery Level 1 total distance covered (p: .041 and .010, respectively). Present findings indicate that the implementation of home-based training programs during confinement periods could be sufficient stimulus to maintain body composition and physical performance (i.e., strength, vertical jump, and sprint), although they might not be sufficient to maintain intermittent endurance capacity in elite female football players.